THE CORRELATION OF KNOWLEDGE AND ATTITUDE WITH BALANCED NUTRITION BEHAVIOR IN STUDENTS DURING THE COVID-19 PANDEMIC : Revisi (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2022)
ABSTARCTIntroduction: Currently, Indonesia is experiencing the COVID-19 pandemic which causes changes in various sectors of life, especially groups of the college student. Changes such as lecture activities and other activities carried out at home affect student knowledge which can affect students' balanced nutritional attitudes and behavior. Objectives: this study aims to determine the correlation of knowledge and attitude with balanced nutrition behavior in college students during pandemic. Methods: This study used a cross-sectional design. The sample of this study was students of the Faculty of Public Health, Hasanuddin University class of 2018-2019, totaling 270 people and selected by using the proportional random sampling technique. The instrument used for the variables of knowledge, attitude, and behavior is a questionnaire. Furthermore, the research results were analyzed by univariate and bivariate with Chi-Square test. Results: from all respondents, it is known that more than some students have good knowledge (54.8%) and positive attitudes (57.4%), and most have well-balanced nutrition behavior (71.9%). Bivariate analysis showed that the p-values ​​related to the relationship between knowledge and attitudes with behavior were 0.062 (p>0.05) and 0.000 (p